Osteoporosis knowledge level of the women living in the city of kirikkale - Aydoğan-Arslan, Saniye; Daşkapan, Arzu; Atalay, Didem K.; Tüzün, Emine Handan; Korkem Yorulmaz, Duygu (Turkish Physiotherapy Association, 2015)
Purpose: Osteoporosis is an important common public health problem among postmenopausal women. Purpose of this study is to research osteoporosis awareness level of the women living in the city of Kirikkale and releationship between awareness level and age and level of education. Methods: 263 women participated to the study. Osteoporosis related risk factors of the participants, such as; socio-demographic data, marital status, occupational status, education level, physical exercise and smoking level were recorded. In accordance with the literature, participants were divided into two groups as young adults (under 45 years) and middle aged (45-64 years). They were also divided according to education levels as; primary education (8 years of education or less) and secondary and higher education (more than 8 years of education). Osteoporosis knowledge level was evaluated by Osteoporosis Self-efficacy Scale Turkish Version and Osteoporosis General Knowledge Score Scale (KOS). Results: Mean age of the participants is 38.98±13.81 year, body mass index (BMI) 27.26±0.39 kg/m2, education level is 8.65±5.16 years. There was positive correlation between Osteoporosis Exercise Self Sufficiency (a subscale of Osteoporosis Self-efficacy Scale), education level (p=0.001; r=0.326), Osteoporosis Exercise Self Sufficiency score and regular exercise (p=0.001). Similarly, There was positive correlation between Osteoporosis Self Sufficiency Scale total score and education level (p=0.001; r=0.293), Osteoporosis Self Sufficiency Scale total score and regular exercise (p=0.001). There was positive correlation between Osteoporosis Calcium Self Sufficiency Subscale (a subscale of Osteoporosis Self-efficacy Scale) score and education level (p=0.006; r=0.170). There was no significant correlation between Osteoporosis Calcium Self Sufficiency Subscale score and regular exercise (p=0.816). Discussion: Our study shows that osteoporosis knowledge level of the women living in Kirikkale increases in parallel to their education level and osteoporosis knowledge levels of younger women are higher.
Kirikkale lnde yaşayan kadinlarin osteoporoz blg düzey
Keywords: Exercise; Knowledge; Osteoporosis; Women